(Re) Locating Subalterns: A Case Study of Nepalese Ethnic Communities - Khanal, Babu Ram (KMC Research Journal, 2018)
The locating process of subalterns is vague and an ever-challenging task that this article attempts to study. This research contends that the determining parameters of subalterns and of privileged class change with a change in space, time and financial status of an individual. So, our perspective of defining subaltern is very superficial, unjust, full with prejudice and impractical that needs to be redefined and reinterpreted. The caste system which has become only a determinants of locating subalterns, can never be a sole determining factor of subaltern. Instead, it is the financial status that should matter while defining the privileged and subalterns. Thus, this paper aims to relocate subalterns in Nepalese ethnic context.